Building Customer Loyalty Through Polimart Customer Satisfaction At Manado State Polytechnic - Mamusung, Robby Tanod; Lumingkewas, Cindy Sandra (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
This study aims to test and explain the effect of customer satisfaction on customer loyalty. The research sample consisted of 100 respondents who were Polimart customers at the Manado State Polytechnic, with a sampling technique using the accidental sampling method. The data collected was analyzed through a series of statistical tests, including instrument validity and reliability tests, linearity tests, simple regression analysis, and hypothesis tests (t-tests). The results of the analysis show that customer satisfaction has an insignificant negative influence on customer loyalty. This indicates that while customer satisfaction is important, other factors may be more dominant in influencing customer loyalty. These findings provide insight that the relationship between satisfaction and loyalty is not always linear or direct, especially in the context of Polimart. This research suggests that Polimart re-evaluate the factors that can increase customer loyalty more effectively. For example, paying attention to aspects of the overall customer experience, offering attractive loyalty programs, or creating a strong emotional connection between customers and brands. Thus, managers can design more comprehensive marketing strategies to increase customer loyalty, regardless of the level of satisfaction felt. These findings also open up further research opportunities to explore other factors that may be more significant in influencing customer loyalty in educational retail environments such as Polimart.